“YOU EITHER LOVE IT IMMEDIATELY, OR YOU HATE IT” REFLECTIONS AND EXPERIENCES OF ESTONIAN EMPLOYEES WITH MICROCHIP IMPLANTS - Siibak, Andra; Otsus, Marleen (AoIR Selected Papers of Internet Research, 2020)
Although employers around the world (e.g. USA, Mexico, Sweden, Belgium, Estonia) have started to implant employees with microchips (Esfola, 2018; Petersen 2019), there is still not enough empirical insights about the opportunities and risks microchipped employees associate with the technology. Semi-structured individual interviews with microchipped employees (n=14) from six different organizations in Estonia were carried out in autumn 2019 so as to contribute new knowledge in this realm and to explore the reasoning of employees with implantables for accepting microchip implants from their employers and the potential benefits and problems they associate with the technology. Relying on the diffusion of innovations theory (DOI) by Everett Rogers (1962 [2003]) the current presentation aims to trace the five steps of the innovation-decision process our interviewed employees underwent when adopting to microchip implants. Preliminary findings indicate that micro-chipped employees are technology enthusiasts who are eager to embrace various technological affordances and have a lot of faith and trust both in the organization they work for. In fact, they were totally unconcerned about the potential problems microchips could pose and wholeheartedly believed in the value of trade-off between convenience and privacy.